Preventing mass atrocities : policies and practices - Harff, Barbara, 1942-; Gurr, Ted Robert, 1936- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
What can be done to warn about and organize political action to prevent genocide and mass atrocities? The international contributors to this volume are either experts or practitioners, often both, who have contributed in substantial ways to analyzing high risk situations, recommending preventive policies and actions, and in several instances helping to organize remedial actions. Whereas current literature on the prevention of genocide is theoretically well grounded, this book explores what can be done, and has been done, in real-world situations. Recommendations and actions are rooted in a generation of experience, based on solid historical, comparative, and empirical research and with a grounding in quantitative methods. This volume examines historical cases to understand the general causes and processes of mass violence and genocide, and engages with ongoing genocidal crises including Darfur and Syria, as well as other forms of related violence such as terrorism and civil conflict. It will be key reading for all students and scholars of genocide, war and conflict studies, human security and security studies in general.
OCLC-licensed vendor bibliographic record.
Keywords: Genocide -- Prevention; Crimes against humanity -- Prevention; Humanitarian intervention; International relations; SOCIAL SCIENCE / Criminology; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Political Freedom & Security / International Security